Knowable Conspiracies: Ideology and Form in Jonathan Franzen’s The Twenty-Seventh City - Jesús Blanco Hidalga, (Miscelánea: A Journal of English and American Studies, 2015)
The narrative work of American novelist Jonathan Franzen has undeniably been neglected by academic criticism, a circumstance which is even more evident as regards his early fiction. It is the case that a significant part of such (scarce) critical attention as there is has focused on political questions and has generally dismissed Franzen’s professedly progressive engagement as unsound and counter-productive. This article departs from that reception —to which it acknowledges a point— and seeks to complement it by providing a wider ideological analysis of Franzen’s first novel. With this aim, we relate the novel to its specific historical and cultural context and we explore its Utopian content in the light of Jameson’s theory of narrative. In addition, we address the political import inherent in the particular novelistic form used by Franzen, a process which involves questioning the generally accepted accounts of Franzen’s stylistic evolution from postmodernism to realism.